2020
DOI: 10.1016/j.molp.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Plant Prime Editors Enable Precise Gene Editing in Rice Cells

Abstract: Prime editing events revealed by next-generation sequencing (NGS). (D) Quantification of prime editing frequencies by PPE3b-V01 at five target sites. (E) Editing events revealed by NGS reads. (F) Schematics of the expression vectors of Plant Prime Editor 3 or 2-Version 2 (PPE3/2-V02). (G-I) Comparison of multiple PBS-RT pairs of different lengths for directing TCA insertion at the OsPDS target site, directing C to A base change at the OsDEP1 target site and directing TGA insertion at the OsDEP1 target site, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(128 citation statements)
references
References 15 publications
3
120
2
3
Order By: Relevance
“…Very recently, several reports have shown that prime editing can be applied to cereal plants Lin et al, 2020;Tang et al, 2020;Xu et al, 2020a;Xu et al, 2020b;Butt et al;Hua et al). All these studies showed that the efficiency of PPEs greatly varies between target sites and is sensitive to several parameters such as both the PBS and RT sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, several reports have shown that prime editing can be applied to cereal plants Lin et al, 2020;Tang et al, 2020;Xu et al, 2020a;Xu et al, 2020b;Butt et al;Hua et al). All these studies showed that the efficiency of PPEs greatly varies between target sites and is sensitive to several parameters such as both the PBS and RT sequence.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the prime editing tool could precisely edit the transgenic reporter and endogenous gene in rice. During the preparation and review of our manuscript, several other prime editing systems in rice and wheat were reported (Li et al, 2020;Lin et al, 2020;Tang et al, 2020;Xu et al, 2020a;Xu et al, 2020b). Tang and colleagues presented data from rice protoplasts only and did not obtain any stable transgenic lines with editing events (Tang et al, 2020), whereas 1-3 rice endogenous genes were edited with relatively low efficiencies in transgenic plants in the other studies.…”
Section: Dear Editormentioning
confidence: 97%
“…Tang and colleagues presented data from rice protoplasts only and did not obtain any stable transgenic lines with editing events (Tang et al, 2020), whereas 1-3 rice endogenous genes were edited with relatively low efficiencies in transgenic plants in the other studies. It is possible that the editing efficiency of the prime editing system can be improved by using other reverse transcriptases (Stamos et al, 2017) or modifying the transgene selection system (Li et al, 2019) to make the prime editors powerful tools for precision molecular breeding of crops.…”
Section: Dear Editormentioning
confidence: 99%
“…Recently, a novel and universal precision genome-editing technology named prime editing was developed and tested in mammalian cells [1]. More recently, seven groups reported applications of prime editors (PE) in rice and wheat, and six groups achieved prime-edited rice lines [2][3][4][5][6][7][8]. Excluding the data based on enriching strategies or that are unsuitable for comparison, a total of 164 prime-edited rice lines transformed with 39 prime editors targeting 11 endogenous rice genes were generated in these previous reports [2,3,5,6,8].…”
Section: Introductionmentioning
confidence: 99%